2010
DOI: 10.1038/ajg.2010.23
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Neutrophil Gelatinase-Associated Lipocalin Is an Early Predictor of Severity and Outcome in Acute Pancreatitis

Abstract: OBJECTIVES About 210,000 new cases of acute pancreatitis (AP) involving reversible inflammation of the pancreas are reported in the United States every year. About one-fourth of all patients with AP go on to develop severe acute pancreatitis (SAP), which, unlike uncomplicated or mild acute pancreatitis (MAP, usually a self-limiting disease), constitutes a life-threatening condition with systemic complications, chiefly multiorgan dysfunction. An early prediction of the severity and outcome of patients with acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 41 publications
1
29
0
1
Order By: Relevance
“…While Lcn-2 correlates with other markers of inflammation, it does not appear to significantly distinguish between UC and CD. 43 Furthermore, Lcn-2 can be elevated in other conditions such as kidney disease, 44 ovarian cancer, 45 acute pancreatitis, 46 Chronic Obstructive Pulmonary Disease (COPD), 47 and cardiovascular disease 48 which limits its utility as an IBD specific biomarker.…”
Section: Current Use Of Biomarkersmentioning
confidence: 99%
“…While Lcn-2 correlates with other markers of inflammation, it does not appear to significantly distinguish between UC and CD. 43 Furthermore, Lcn-2 can be elevated in other conditions such as kidney disease, 44 ovarian cancer, 45 acute pancreatitis, 46 Chronic Obstructive Pulmonary Disease (COPD), 47 and cardiovascular disease 48 which limits its utility as an IBD specific biomarker.…”
Section: Current Use Of Biomarkersmentioning
confidence: 99%
“…Pancreatic disease is highly prevalent in Western countries, with a combined annual incidence of more than 2 million people in the United States alone [1–3]. Pancreatic diseases are clinically difficult to conclusively diagnose, as signs and symptoms consistent with a particular pancreatic etiology frequently overlap with multiple others, as is the case with chronic pancreatitis (CP) and pancreatic cancer (PC), to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, several studies have identified induction of NGAL in acute and chronic kidney injury, cardiovascular disease, transplantation, sepsis, chronic obstructive pulmonary disease, pancreatitis, and various cancers [8,16,17]. These findings raise intriguing questions about its correlation with the magnitude of inflammatory response as well as its specificity and sensitivity in assessing various inflammatory conditions.…”
mentioning
confidence: 95%